Langeweile und Muße: Pascal - Augustinus - Aristoteles - Wagner, Patrick (2021)
The doctoral thesis examines the philosophical-historical interrelations between boredom and leisure. It follows the central hypothesis that both boredom and leisure express in a mirrored way a reflexive relationship of the human being to the self and the world, sharing a connecting element in their ontological reference to the absolute, i.e., God or the divine. The topics are presented in a threefold structure: Beginning with the modern position of Blaise Pascal and focusing on boredom (ennui), followed by the early Christian and late ancient view of the neo-platonic theologian and philosopher Augustine of Hippo, dealing with curiosity (curiositas) as the dialectical counterpart to boredom, and concluding with the ancient perspective of Aristotle, which has leisure (scholē) as its subject. This inverted chronological arrangement of the three authors and the subject areas is methodologically justified, referring to the effective historical and hermeneutical perspective of the thesis: Starting from the most recent and best-known position of understanding boredom primarily as a psychological phenomenon, it is shown that even this seemingly purely psychological phenomenon has a historical dimension and is ontologically based. From there on, the historical and philosophical references to Augustine’s curiosity are presented, to finally juxtapose the dualism of ennui and curiositas with the psychological, historical, and ontological dimensions of leisure in Aristotle. Thus, the actual hermeneutic gain of the thesis consists in revealing the psychological, historical and, above all, ontological depth layers of boredom and leisure, which in particular broadens the view for the more recent philosophical discussions of the phenomena.